2007
DOI: 10.1890/06-1067.1
|View full text |Cite
|
Sign up to set email alerts
|

Forest Structure and Light Regimes Following Moderate Wind Storms: Implications for Multi-Cohort Management

Abstract: Moderate-severity disturbances appear to be common throughout much of North America, but they have received relatively little detailed study compared to catastrophic disturbances and small gap dynamics. In this study, we examined the immediate impact of moderate-intensity wind storms on stand structure, opening sizes, and light regimes in three hemlock-hardwood forests of northeastern Wisconsin. These were compared to three stands managed by single-tree and group selection, the predominant forest management sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
128
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 163 publications
(137 citation statements)
references
References 64 publications
9
128
0
Order By: Relevance
“…In forest ecosystems, LIDs typically damage trees across several tens to hundreds of thousands of hectares or more, inflicting widespread catastrophic damage approaching or exceeding 70% canopy loss (Canham and Loucks 1984, Foster and Boose 1992, Hanson and Lorimer 2007. However, LIDs may also damage a significantly smaller area of trees depending on the location and characteristics of specific disturbances, necessitating explicit descriptions of disturbance size, intensity, and recurrence interval applicable for disparate regions and disturbance types (Foster et al 1998).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In forest ecosystems, LIDs typically damage trees across several tens to hundreds of thousands of hectares or more, inflicting widespread catastrophic damage approaching or exceeding 70% canopy loss (Canham and Loucks 1984, Foster and Boose 1992, Hanson and Lorimer 2007. However, LIDs may also damage a significantly smaller area of trees depending on the location and characteristics of specific disturbances, necessitating explicit descriptions of disturbance size, intensity, and recurrence interval applicable for disparate regions and disturbance types (Foster et al 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Hence, one might surmise that more frequently occurring intermediate disturbances also play a pivotal role in shaping complex mosaics of trees on forested landscapes (Woods 2004, Busby et al 2009). In fact, intermediate disturbances may damage extensive areas, foster the development of landscape heterogeneity, and exert a strong influence on species composition, structure, demography, and ecosystem processes (Frelich and Lorimer 1991a, Dyer and Baird 1997, Boose et al 2001, White and Jentsch 2001, Woods 2004, Hanson and Lorimer 2007. Compared to LIDs, damage from intermediate disturbances tends to be patchier, less catastrophic, and usually occurs over tens of thousands of hectares or less.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The diagonal lines between the rare, large-scale and more frequent, small-scale ovals are a reference for the bounds (longest return interval and smallest scale) of each forest type's natural disturbance regime. The Northeastern hardwood diagram modifies one in Seymour et al (2002), adding a hypothesized intermediate disturbance regime suggested by recent research (Millward and Kraft 2004;Woods 2004;Hanson and Lorimer 2007) some researchers (Hunter 1999;Lindenmayer and Franklin 2002) have suggested using to evaluate management activities. In addition to Seymour et al's (2002) choice of scale and frequency, we suggest a third evaluation criterion, the level of biological legacies left by historic disturbances.…”
Section: Comparing Management Practices To Natural Disturbancesmentioning
confidence: 98%
“…>10 ha). However, recent studies suggest that intermediate intensity disturbances, such as ice storms and microburst wind events, may be more prevalent than previously recognized (Ziegler 2002;Millward and Kraft 2004;Woods 2004;Hanson and Lorimer 2007). These events tend to produce partial to high canopy mortality across a moderate to large sized area, but they can leave abundant residual live and dead or damaged trees (Keeton unpublished data).…”
Section: Northern Hardwood Regionmentioning
confidence: 99%